The Possibility of Using Paulownia elongata S. Y. Hu × Paulownia fortunei Hybrid for Phytoextraction of Toxic Elements from Post-Industrial Wastes with Biochar - Kinga Drzewiecka; Monika Gąsecka; Zuzanna Magdziak; Sylwia Budzyńska; Małgorzata Szostek; Przemysław Niedzielski; Anna Budka; Edward Roszyk; Beata Doczekalska; Marta Górska; Mirosław Mleczek (Plants, 2021)
The potential of the Paulownia hybrid for the uptake and transport of 67 elements along with the physiological response of plants cultivated in highly contaminated post-industrial wastes (flotation tailings—FT, and mining sludge—MS) was investigated. Biochar (BR) was added to substrates to limit metal mobility and facilitate plant survival. Paulownia could effectively uptake and translocate B, Ca, K, P, Rb, Re and Ta. Despite severe growth retardation, chlorophyll biosynthesis was not depleted, while an increased carotenoid content was noted for plants cultivated in waste materials. In Paulownia leaves and roots hydroxybenzoic acids (C6-C1) were dominant phenolics, and hydroxycinnamic acids/phenylpropanoids (C6-C3) and flavonoids (C6-C3-C6) were also detected. Plant cultivation in wastes resulted in quantitative changes in the phenolic fraction, and a significant drop or total inhibition of particular phenolics. Cultivation in waste materials resulted in increased biosynthesis of malic and succinic acids in the roots of FT-cultivated plants, and malic and acetic acids in the case of MS/BR substrate. The obtained results indicate that the addition of biochar can support the adaptation of Paulownia seedlings growing on MS, however, in order to limit unfavorable changes in the plant, an optimal addition of waste is necessary.